2023
DOI: 10.2196/44132
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Digital Health Interventions Containing Game Components for the Self-management of Type 2 Diabetes: Systematic Review

Linda Ossenbrink,
Tina Haase,
Patrick Timpel
et al.

Abstract: Background Games and game components have become a major trend in the realm of digital health research and practice as they are assumed to foster behavior change and thereby improve patient-reported and clinical outcomes for patients with type 2 diabetes. Objective The aim of this systematic review was to summarize and evaluate the current evidence on the effectiveness of digital health interventions containing game components on behavioral, patient-rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Comparably, other systematic reviews have shown that interventions promoting a healthy lifestyle yield modest but positive behavioral shifts and have a significant, albeit small, impact on clinical endpoints, mirroring outcomes from other computer-based interventions 29,30 . Exergames designed to encourage physical activity 31 have been credited with improving fitness-related outcomes and, to a lesser extent, clinical health parameters and overall wellbeing 32 . Furthermore, a scoping review has recognized the broad application spectrum of health education games, though it emphasized the necessity for sustained efficacy evaluations 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparably, other systematic reviews have shown that interventions promoting a healthy lifestyle yield modest but positive behavioral shifts and have a significant, albeit small, impact on clinical endpoints, mirroring outcomes from other computer-based interventions 29,30 . Exergames designed to encourage physical activity 31 have been credited with improving fitness-related outcomes and, to a lesser extent, clinical health parameters and overall wellbeing 32 . Furthermore, a scoping review has recognized the broad application spectrum of health education games, though it emphasized the necessity for sustained efficacy evaluations 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, government blood donation apps in countries such as the United States and Canada have integrated gamified elements into their ICT services, aiming to boost donor motivation [ 16 , 17 ]. Although the impact on blood donation is yet to be studied, gamification has proven effective in therapy commitment and health self-monitoring [ 18 , 19 ]. Considering this, gamification holds promise for increasing motivation in the blood donation context.…”
Section: Introductionmentioning
confidence: 99%